Conectados, educados financeiramente e empreendedores: uma análise sob a ótica da prontidão tecnológica e da aceitação e uso de tecnologias - Melo, Wilton Alexandre de (2025)
This study aimed to analyze the influence of technological readiness and the acceptance and use of technologies on the Personal Financial Management and entrepreneurial behavior of private company managers, as well as the influence of Personal Financial Management on the Characteristics of Entrepreneurial Behavior. The methodological procedures adopted in this thesis involve the following points: in terms of objectives, this is a descriptive and explanatory study; in terms of the approach to the problem, it is characterized as being quantitative in nature; in terms of procedures, the study was designed as a survey. With regard to the choice and definition of the population and sample, due to the need to obtain a sample robust enough for analysis and reflection on the subject, managers of private companies at various levels were considered, from companies housed in the main shopping centers in the state of Paraíba, especially those located in the two largest municipalities: Campina Grande and João Pessoa. For the analysis, in addition to descriptive statistics, in order to put together a panorama of analysis, Spearman's Correlation was used, followed by Confirmatory Factor Analysis and Structural Equation Modeling. Data was collected through the direct application of questionnaires and voluntary participation through the provision of a Free and Informed Consent Form (FICF) before answering the questionnaire, guaranteeing the confidentiality of the respondents. The main results were as follows: both Technological Readiness and the theoretical model of Acceptance and Use of Technologies have an influence on the constructs and dimensions of Personal Financial Management and the Characteristics of Entrepreneurial Behavior. From personal and interpersonal behavioral perspectives, individuals understand the importance of the technological apparatus when it comes to decision-making in personal finance, as well as in the development of any entrepreneurial activity. However, in contrast to what is presented in the literature, Personal Financial Management, for the sample analyzed, has no influence on the Characteristics of Entrepreneurial Behavior, even though there is an understanding that technologies optimize the individual aspects of each of the two approaches presented. Finally, briefly: the influence of Technological Readiness permeates its motivational dimensions (Optimism and Innovativeness) for both Personal Financial Management and the Entrepreneurial Characteristics presented, while UTAUT/2012 influences the personal finance and entrepreneurial aspects presented in all its dimensions. If studies are carried out on the Characteristics of Entrepreneurial Behavior, the most adherent theoretical basis is Technological Readiness. On the other hand, if the analysis focuses on aspects of Personal Financial Management, the UTAUT/2012 model is more suitable for use in the studies. Another particularity is the knowledge that in order to have good entrepreneurial skills, it is necessary first of all to have excellent personal finance skills, even though this fact was not evident in the sample analyzed.